Role of blood-borne factors in sympathoexcitation-mediated hypertension: Potential neurally mediated hypertension in preeclampsia - ISSOTINA, Abdoulaye Zibrila; SANGARE, Machioud; Zheng Wang, Ming Zeng; Xiaoxu, Liu (My University, 2023)
Hypertension remains a threat for society due to its unknown causes, preventing proper management, for the growing number of patients, for its state as a high-risk factor for stroke, cardiac and renal complication and as cause of disability. Data from clinical and animal researches have suggested the important role of many soluble factors in the pathophysiology of hypertension through their neuro-stimulating effects. Central targets of these factors are of molecular, cellular and structural nature. Preeclampsia (PE) is characterized by high level of soluble factors with strong pro-hypertensive activity and includes immune factors such as proinflammatory cytokines (PICs). The potential neural effect of those factors in PE is still poorly understood. Shedding light into the potential central effect of the soluble factors in PE may advance our current comprehension of the pathophysiology of hypertension in PE, which will contribute to better management of the disease. In this paper, we summarized existing data in respect of hypothesis of this review, that is, the existence of the neural component in the pathophysiology of the hypertension in PE. Future studies would address this hypothesis to broaden our understanding of the pathophysiology of hypertension in PE.
Keywords: Keywords; Hypertension; Neurally mediated hypertension; Preeclampsia; Placental derived pro-hypertensive factors